Use of tissue ink to maintain identification of individual cores on needle biopsies of the prostate. Issue 9 (19th July 2008) - Singh, P B; Saw, N K; Haq, A; Blades, R A; Martin, F L; Matanhelia, S S; Nicholson, C M
Abstract : Background: There is an increasing necessity to extract the maximum amount of information, beyond even a cancer diagnosis, from prostate biopsies. Thus, maintaining site-specific information regarding individual biopsy cores might be critical. Aim: To evaluate the applicability of employing tissue ink to maintain the identity of individual prostatic biopsy cores. Method: In this ongoing study, 12 core prostate biopsy specimens are sent to the laboratory in individual pots labelled according to anatomical site. The specimens are placed in two separate multi-compartment cassettes. They are inked with different colours to identify the site of origin from each lobe. The cassettes are then processed with a single paraffin block for each side; the six cores from each side can be mounted on a single slide. Results: The different colours used adhere well to the biopsy cores, thus maintaining the identity of each core. Six cores from each side are embedded in a single paraffin block and examined on a single slide, making it cost-effective, while maintaining high quality, accurate histopathological information. Conclusion: Differential inking of prostate biopsy cores is an easily applicable method that is cost-effective and provides tumour location information. Prostate biopsy data archived to maintain individual core information might be used to determine applicability of such information to predict extra-capsular extension by correlating with imaging and radical prostatectomy findings, and for treatment planning.